The effect of children on specialization and coordination of partners' activities - Anh Tram Le; Paul W. Miller (Institute for the Study of Labor (IZA), 2010)
This paper first documents the extent of the specialization in time use in couple families, and the impact of children on this specialization. It then examines the links between the time allocations of partners in couple families, the impact of children on these links, and the effects these factors have on specialization in time use. Children are shown to intensify the specialization in time use in couple families through reducing the apparent complementarity in time allocations of their parents.
Keywords: J13; J16; J22; 330; Time allocations; gender; specialisation; coordination